Omphaloplasty A Surgical Guide of the Umbilicus (Springer International Publishing, 2018)
This book offers an essential guide to surgical approaches to the umbilicus. The navel is the only natural scar in the body, accepted for all human beings all over the world. Its absence or distortions can have negative psychological impacts, as it normally lends beauty and harmony to the otherwise unattractive abdomen. The aesthetic importance of the navel justifies the increasing amount of individuals undergoing abdominoplasty and omphaloplasty. However, these surgeries may lead to a series of complications or unintended aesthetic outcomes. Indeed, the postsurgical final aspect of the umbilicus is the main stigma and primary source of problems and complaints following abdominoplasty. In this book readers will find a complete surgical guide to the most important surgical approaches and strategies related to the navel, helping them to deliver a high standard of quality and patient-tailored surgical and aesthetic outcomes. Written by a renowned plastic surgeonswith more than 20 years of experience, Omphaloplasty - A Surgical Guide of the Umbilicus offers readers an overview of general and innovative surgical techniques for the umbilicus, helping them to make the best choice when performing abdominoplasties.